Multiple Multilateral Coronary-Cameral Fistulae in a Patient with Minor Cardiac Venous System. (6th February 2014) - Markota, Darko; Prskalo, Zrinko; Markota, Ivica; Starcevic, Boris; Maskovic, Josip; Tomic, Monika; Brizic, Ivica
Abstract : A 40-year-old man was hospitalized in the coronary care unit with chest pain and abnormal electrocardiogram. Twenty days earlier, the patient underwent laparoscopic gallbladder surgery. Due to chest pain and ischemic ECG changes, patient was subjected to coronary angiography. The selective coronary angiography revealed multiple multilateral fistulae arising from the left anterior descending artery, circumflex artery, and the right coronary artery draining to the left ventricle. Multislice computed tomography showed hypoplastic coronary sinus and minor cardiac venous system.